# 4ab-12abc=

## Simple and best practice solution for 4ab-12abc= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 4ab-12abc= equation:

Simplifying
4ab + -12abc = 0
Solving
4ab + -12abc = 0
Solving for variable 'a'.
Move all terms containing a to the left, all other terms to the right.
Factor out the Greatest Common Factor (GCF), '4ab'.
4ab(1 + -3c) = 0
Ignore the factor 4.
Subproblem 1Set the factor 'ab' equal to zero and attempt to solve:
Simplifying
ab = 0
Solving
ab = 0
Move all terms containing a to the left, all other terms to the right.
Simplifying
ab = 0
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
Subproblem 2Set the factor '(1 + -3c)' equal to zero and attempt to solve:
Simplifying
1 + -3c = 0
Solving
1 + -3c = 0
Move all terms containing a to the left, all other terms to the right.
Add '-1' to each side of the equation.
1 + -1 + -3c = 0 + -1
Combine like terms: 1 + -1 = 0
0 + -3c = 0 + -1
-3c = 0 + -1
Combine like terms: 0 + -1 = -1
-3c = -1
Add '3c' to each side of the equation.
-3c + 3c = -1 + 3c
Combine like terms: -3c + 3c = 0
0 = -1 + 3c
Simplifying
0 = -1 + 3c
The solution to this equation could not be determined.
This subproblem is being ignored because a solution could not be determined.
The solution to this equation could not be determined.`